2005
DOI: 10.1038/sj.npp.1300728
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Citalopram Pretreatment on Neuronal Responses to Neuropsychological Tasks in Normal Volunteers: An fMRI Study

Abstract: Changes in serotonin neurotransmission have also been implicated in the etiology and treatment of impulse control disorders, depression, and anxiety. We have investigated the effect of enhancing serotonin function on fundamental brain processes that we have proposed are abnormal in these disorders. In all, 12 male volunteers received citalopram (7.5 mg intravenously) and placebo pretreatment in a single-blind crossover design before undertaking Go/No-go, Loss/No-loss, and covert (aversive) face emotion recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
184
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(210 citation statements)
references
References 84 publications
22
184
4
Order By: Relevance
“…This finding was explained in terms of a stronger sensitivity of brain areas involved in the processing of fear stimuli in individuals with a high BIS score, which is possibly mediated by the 5-HT system. The finding that especially the amygdala is responsive to serotonergic manipulations is in line with a number of previous studies reporting modified amygdala responses as a result of 5-HT manipulations (eg Sheline et al, 2001;Fu et al, 2004;Del-Ben et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding was explained in terms of a stronger sensitivity of brain areas involved in the processing of fear stimuli in individuals with a high BIS score, which is possibly mediated by the 5-HT system. The finding that especially the amygdala is responsive to serotonergic manipulations is in line with a number of previous studies reporting modified amygdala responses as a result of 5-HT manipulations (eg Sheline et al, 2001;Fu et al, 2004;Del-Ben et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…ATD generally increased right amygdala activation in the contrast comparing all stimulus events of the TRPÀ condition with all stimulus events in the TRP + condition. The effects of ATD on amygdala activation are in line with findings of several other studies reporting sensitivity of the amygdala to serotonergic manipulations (eg Sheline et al, 2001;Fu et al, 2004;Del-Ben et al, 2005). These findings are also in line with studies reporting an enhanced amygdala response to fearful stimuli in carriers of the short allele variant of a polymorphism in the promoter region of the 5-HT transporter gene (eg Hariri et al, 2002), who are characterized by a lowered 5-HT metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…A relationship between serotonin and attentional control is also supported by studies in rats using the 5 choice serial reaction time task (5-CSRTT) in which enhanced premature responses (a measure of failure of behavioral inhibition) have been noted under conditions of increased serotonin neurotransmission (Dalley et al, 2002;Koskinen et al, 2003;Koskinen and Sirvio, 2001), particularly in the infralimbic/prelimbic regions of the medial prefrontal cortex (Dalley et al, 2002). Similarly, it has been found that increased serotonergic function can increase premature responses in a behavioral inhibition task in healthy humans (Del-Ben et al, 2005). Together these findings suggest that the serotonergic system within specific areas of the cortex may play an important role in attentional control, with reduced serotonergic transmission associated with greater attentional control or behavioral inhibition.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, citalopram attenuated right BA 47 responses but attenuated right amygdala response to aversive faces. 29 Recently, this finding has been replicated in a randomized, placebo-controlled study. 30 Healthy volunteers were given either a single oral dose of citalopram (20 mg) or placebo.…”
Section: Direct Effects Of Psychotropic Medications On Cbf In Healthymentioning
confidence: 84%